(x + 3)(x − 1) = − x + 1 Solve for x.

3 Answers

jeew-m's profile pic

jeew-m | College Teacher | (Level 1) Educator Emeritus

Posted on

`(x+3)(x-1) = -x+1`

`(x+3)(x-1) = -(x-1)`

See that (x-1) term in both sides cancel out.

`(x+3) = -1`

`x = -1-3`

`x = -4`

So the answer is x = -4.

aruv's profile pic

aruv | High School Teacher | (Level 2) Valedictorian

Posted on

It is quadratc equation so it has two roots






`either `






Also we can verify it wth help of graph


f(x)=(x+3)(x-1)+(x-1) The zeros of f(x) is root of equation f(x)=0

f(x) eets x-axis at x=-4 and x=1

user4825270's profile pic

user4825270 | Student | (Level 3) eNoter

Posted on

we expand the brackets
x=-4 or 1